Nanotechnology in therapeutics: a focus on nanoparticles as a drug delivery system. (August 2012) - Bamrungsap, Suwussa; Zhao, Zilong; Chen, Tao; Wang, Lin; Li, Chunmei; Fu, Ting; Tan, Weihong
Continuing improvement in the pharmacological and therapeutic properties of drugs is driving the revolution in novel drug delivery systems. In fact, a wide spectrum of therapeutic nanocarriers has been extensively investigated to address this emerging need. Accordingly, this article will review recent developments in the use of nanoparticles as drug delivery systems to treat a wide variety of diseases. Finally, we will introduce challenges and future nanotechnology strategies to overcome limitations in this field.